(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: To analyse the In Silico Strategy against Adam’s Oliver Syndrome by Predicting RNAi Molecules against Dominant Genes by Suppressing Rho GTPases. Methods: There are six genes known (ARHGAP31, DLL4, NOTCH1, RBPJ, DOCK6, and EOGT) reported so far, which can cause this syndrome. We retrieved CCDS and CDS sequences of each gene from the NCBI database and multiple sequence alignment was performed using ClustalΩ. After target identification, we chose ARHGAP31 as the target gene, as it is a major cause of cutis aplasia, also the regulator of Rho GTPase activity. siRNA and miRNA were designed using Invitrogen Block-iT. Results: The Proteins related to ARHGAP31 were obtained using Blastx. GC content analysis of ARHGAP31 using ENDMEMO was found to be 54.55%, and RNA-RNA interaction was interpreted using IntaRNA. Heat capacity, c = 17.88025 J/kg ºk, was analyzed using OligoCalc server and prediction of secondary structure was done using Modeller 9.22 and SAVES. The dope score, analyzed from the RC plot, for qseq4.B99990004 is –48,617.11328. The Z-score value was calculated using ProSA. The Z-score value for the modeled protein is 9.12. Conclusion: Study indicates that by suppressing Rho GTPase activity of ARHGAP31 gene, we can reduce the occurrence of AOS during early embryonic stages.